2017
DOI: 10.1097/prs.0000000000003521
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting the Buccal Fat Pad Does Not Result in Aesthetic Deformity in Cleft Patients: A Retrospective Analysis

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…The utilization of the BFPF to line large denuded lateral gaps at the gutters of the hard palate to decrease transverse width discrepancy, accelerate healing and increase durability of the repair without long-term residual aesthetic consequences has been previously described by our craniofacial team. 27,31,32 The use of the BFPF, however, as a surgical remedy to fill the void for a large interpositional dead space and to reinforce thin outer and inner lamellae in the anterior soft palate after posterior muscle transposition in wide and challenging cleft repairs has heretofore not been reported. There remains a subset of patients who present with very wide clefts and other challenging anatomic features such as thin and friable mucosal covers which are challenging to close.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of the BFPF to line large denuded lateral gaps at the gutters of the hard palate to decrease transverse width discrepancy, accelerate healing and increase durability of the repair without long-term residual aesthetic consequences has been previously described by our craniofacial team. 27,31,32 The use of the BFPF, however, as a surgical remedy to fill the void for a large interpositional dead space and to reinforce thin outer and inner lamellae in the anterior soft palate after posterior muscle transposition in wide and challenging cleft repairs has heretofore not been reported. There remains a subset of patients who present with very wide clefts and other challenging anatomic features such as thin and friable mucosal covers which are challenging to close.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, multiple authors have demonstrated that use of the fat pad does not have long-term residual aesthetic consequences. 27,32 In this current study, the authors hypothesize that the resultant void that occurs once the levator sling has been retropositioned, particularly in wide and challenging cleft repairs, is responsible for tissue contracture that contributes to palatal shortening and relapse of the muscle position as evidenced as by poorer speech outcomes and increased fistula formation. Filling the void using the BFPF technique as a source of vascularized tissue functions to occupy the large interpositional dead space and reinforce thin outer and inner lamellae in the anterior soft palate after posterior muscle transposition.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Isso provavelmente se deve ao uso restrito apenas da extensão bucal e corpo principal da bola de bichat, de modo que as demais extensões ainda proporcionam um arcabouço para a projeção da bochecha. Em adição, a literatura relata que a exérese do corpo adiposo (lipectomia) para finalidades estéticas possuem efeitos mínimos ou transitórios sobre a projeção da bochecha (Bennett, Thurston, Vercler, Kasten & Buchman, 2017).…”
Section: Discussionunclassified
“…In these scenarios, the buccal fat pad flap can cover the raw surface and at least partially minimize the secondary healing process with fibrosis. [27,34] In the literature, different authors have described modified lateral relaxing incisions (e.g., only a small incision lateral to the hamulus) while others have reported palatoplasty without lateral relaxing incisions. [30,[35][36][37][38][39][40][41][42][43][44][45] Overall, the described benefits of these modified surgical approaches lies on the absence of exposed raw surface or healing by secondary intention, supposedly reducing perioperative contamination, bleeding, and pain and also minimizing postoperative scarring and bone growth interference.…”
Section: Discussionmentioning
confidence: 99%